What causes prescribing errors in children? Scoping review. Issue 8 (10th August 2019) - Conn, Richard L; Kearney, Orla; Tully, Mary P; Shields, Michael D; Dornan, Tim
Abstract : Objectives: (1) Systematically assemble, analyse and synthesise published evidence on causes of prescribing error in children. (2) Present results to a multidisciplinary group of paediatric prescribing stakeholders to validate findings and establish how causative factors lead to errors in practice. Design: Scoping review using Arksey and O'Malley's framework, including stakeholder consultation; qualitative evidence synthesis. Methods: We followed the six scoping review stages. (1) Research question—the research question was 'What is known about causes of prescribing error in children?' (2) Search strategy—we searched MEDLINE, EMBASE, CINAHL (from inception to February 2018), grey literature and reference lists of included studies. (3) Article selection—all published evidence contributing information on the causes of prescribing error in children was eligible for inclusion. We included review articles as secondary evidence to broaden understanding. (4) Charting data—results were collated in a custom data charting form. (5) Reporting results—we summarised article characteristics, extracted causal evidence and thematically synthesised findings. (6) Stakeholder consultation—results were presented to a multidisciplinary focus group of six prescribing stakeholders to establish validity, relevance and mechanisms by which causes lead to errors in practice. Results: 68 articles were included. We identified six main causes of prescribing errors: children's fundamental differences led to individualised dosing and calculations; off-licence prescribing; medication formulations; communication with children ; and experience working with children . Primary evidence clarifying causes was lacking. Conclusions: Specific factors complicate prescribing for children and increase risk of errors. Primary research is needed to confirm and elaborate these causes of error. In the meantime, this review uses existing evidence to make provisional paediatric-specific recommendations for policy, practice and education.